2010
DOI: 10.1142/s0192415x1000810x
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and Anti-Inflammatory Activities of the Aqueous Extracts from ThreeFlemingiaSpecies

Abstract: I-Tiao-Gung has long been used in the Kinmen area of Taiwan as an anti-inflammatory agent for the treatment of rheumatic illness. The roots of Flemingia lineata (FL), Flemingia macrophylla (FM) and Flemingia prostrata (FP) are also used as I-Tiao-Gung in the Taiwan markets. In the present study, we investigated the analgesic effect of aqueous extracts of Flemingia lineata (FL), Flemingia macrophylla (FM), and Flemingia prostrata (FP) by acetic acid-induced writhing response, formalin test, and the anti-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The anti-inflammatory activity of F. macrophylla crude extract has been recently reported [11]. The authors utilized λ-carrageenan to induce inflammation and paw edema in mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The anti-inflammatory activity of F. macrophylla crude extract has been recently reported [11]. The authors utilized λ-carrageenan to induce inflammation and paw edema in mice.…”
Section: Resultsmentioning
confidence: 99%
“…The authors utilized λ-carrageenan to induce inflammation and paw edema in mice. The inflammation response has been linked to the neutrophils’ infiltration and the production of neutrophil-derived free radicals [11]. There is considerable evidence from clinical and experimental studies that the recruitment of neutrophils into joints is a critical hallmark of rheumatoid arthritis [40,41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that Flemingia macrophylla extract (FME) shows analgesic and anti-inflammatory activities in mice [12] as well as antioxidant and hepatoprotective effects in rats [13]. Furthermore, the flavonoids in Flemingia macrophylla have been demonstrated to inhibit A β -induced neurotoxicity [11].…”
Section: Introductionmentioning
confidence: 99%
“…The stems or leaves have been used as an anti-inflammatory, blood circulation promotion and antidiabetic agent, all of which were relevant to the pathogenesis of Alzheimer's disease (AD). Recent research has suggested its neuroprotective activity against amyloid β (A β ) [3], hepatoprotective activity [4], antiinflammatory activity [5], and antiosteoporosis activity [6]. …”
Section: Introductionmentioning
confidence: 99%